Bioinformatic characterization and production of L-asparaginase from Bacillus sp. M62 isolated from the Maras saltern, Cusco, Peru - Calderón-Toledo, Susana (2023)
The aim of this study was to perform bioinformatics characterization and optimize the production of extracellular L-asparaginase from Bacillus sp. M62, isolated from the Maras salt ponds (Cusco). To achieve this, the production of L-asparaginase was verified by the change in color of modified M9 medium, containing 0.0075% bromophenol blue, at pH 7.4 and 37°C for 72 hours. Genomic DNA was extracted to amplify the 16S ribosomal genes and the ansA3 gene. The amino acid sequence encoded by the ansA3 gene was predicted using bioinformatic analysis. The production of intracellular and extracellular L-asparaginase was evaluated at different levels of glucose, L-asparagine, NaCl, and pH in modified M9 medium. Additionally, the enzymatic activities of L-asparaginase and L-glutaminase were determined by quantifying the released ammonium using the Nessler method. Bacillus sp. M62 showed the change in color of the modified M9 medium, high similarity, and evolutionary closeness to Bacillus licheniformis. The amplified ansA3 gene was found to encode for 319 amino acids, with a predicted active site pattern (GFVITHGTDTM) and 15 immunogenic sites. The production of extracellular L-asparaginase was found to be higher than intracellular L-asparaginase and was optimized from 0.37 U/mL (0.24 U/mg) to 2.15 ± 0.39 U/mL (0.63 U/mg). Finally, it was found that Bacillus sp. M62 presents extracellular L-asparaginase with minimal L-glutaminase activity.